Big Data: Behind The Scenes - Kaustubh Vaghmare
The phrase "big data" has become a highly common phrase in recent times. However the phrase 'big data', while it may have been coined to indeed vaguely refer to large volumes of data, has now evolved to mean something much more specific. The phrase 'big data" actually refers to a family of technologies, platforms, software and techniques aimed at solving a variety of problems otherwise untenable through conventional or traditional solutions. The present article summarizes a traditional approach to a data management problem and presents limitations of this approach. The three 'Vs' used to characterize and define 'big data' are then elucidated upon. Finally, the article summarizes commonly used tools and technologies to solve the `big data' problem.
Keywords: Astronomy